Charitable giving, social capital and positional concerns - Armenak Antinyan; Vardan Baghdasaryan; Aleksandr Grigoryan (Cardiff University, Cardiff Business School, 2021)
Research on the effects of positional concerns on individuals' attitudes and behavior in certain policy-relevant areas is lacking. In this paper, we investigate the relationship between positional concerns, charitable giving and social capital. We use data from the 'Caucasus Barometer' survey administered in three post-Soviet transition economies: Armenia, Azerbaijan, and Georgia. Our analysis proceeds in two phases. First, controlling for absolute income and other individual and household characteristics, we show an association between positional concerns and charitable giving as well as between positional concerns and social capital. Second, we use an instrumental variable model that uses heteroskedasticity-based instruments generated through Lewbel's method to provide supporting evidence of the causal impact of positional concerns on the outcome variables of interest. We find that the relative deprivation of a household can have negative impacts on its members' charitable giving and social capital.
Keywords: D31; D63; D91; P30; Z13; 330; Positional Concern; Social Capital; Charitable Giving; Reference Group